PEDAGOGICAL FEATURES OF GROUND TRAINING IN COMBAT FLIGHTS OF FUTURE TACTICAL AVIATION PILOTS - Невзоров, Роман Вікторович (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2020)
In the article that is the publication of separate positions of doctoral dissertation research, authorial conceptual vision of problem of surface studies to battle flights (surface battle studies) of future pilots of tactical aviation is presented. It is important the constituent of professional preparation of soldiery pilots practically was not investigated from positions of professional aviation pedagogics and military pedagogics. Forming primary readiness future of soldiery pilots to own flying studies and implementation of urgent flying tasks, surface studies to battle flights mortgage foundation on the future for effective professional activity. An aim and tasks to the article is a ground of surface studies to battle flights of future pilots of tactical aviation as new separate direction of military pedagogics and selection of him pedagogical features. On the basis of complex of the scientific, special pedagogical and empiric methods, an author examines him as an independent pedagogical construction fundamentally different from methodology of flying studies and surface preparation to flights. It is suggested to define surface studies to battle flights of future pilots of tactical aviation as a division of military-pedagogical science, that investigates conformities to law of forming on earth of personality, battle activity of that comes true midair and grounds maintenance, forms and methods of the system of surface education, studies and education on the whole future pilots of tactical aviation. Distinguished and reasonable her basic pedagogical features - integration and multilevel character of surface studies to battle flights of future pilots of tactical aviation